Assessing pteropod shell dissolution to advance ocean monitoring techniques: a methods comparison of SEM, CT, and light microscopy - Koester, Bryce E.; Handley, John C.; Mercado, Maven; Goodchild, Owen A.; Oakes, Rosie L.; Sessa, Jocelyn A. (Frontiers in Marine Science, 2025)
Pteropods are marine planktonic snails that are used as bioindicators of ocean acidification due to their thin, aragonitic shells, and ubiquity throughout the world’s oceans; their responses include decreased size, reduced shell thickness, and increased shell dissolution. Shell dissolution has been measured with a variety of metrics involving light microscopy, scanning electron microscopy (SEM), and computed tomography (CT). While CT and SEM metrics offer high resolution imaging, these analyses are cost- and time-intensive relative to light microscopy analysis. This research compares light microscopy, CT, and SEM shell dissolution metrics across three pteropod species: Limacina helicina, Limacina retroversa, and Heliconoides inflatus. Sourced from multiple localities, these specimens lived in tropical to subpolar environments and were exposed to varying aragonite saturations states due to oceanographic differences in these environments. Specimens were evaluated with light microscopy for the Limacina Dissolution Index (LDX), with SEM for percent of pristine shell coverage and maximum dissolution type, and with CT for whole-shell thickness. LDX and the percentage of pristine shell determined via SEM were highly correlated in all three species’ datasets. For L. retroversa, LDX was also significantly correlated to SEM maximum dissolution type. Although the genera Heliconoides and Limacina have different shell microstructures, the relationship between LDX and SEM dissolution did not vary by species. The CT metric for shell thickness was not significantly correlated to any other dissolution metrics for any species. However, severely dissolved areas apparent in SEM were visually discernible in CT thickness heatmaps. While CT may not detect minor shell dissolution, previous studies have used CT to detect reduced calcification in response to ocean acidification. SEM is ideal for detecting the onset of dissolution, but SEMing large numbers of specimens may not be practical due to monetary and time constraints. LDX, on the other hand, is a fast and cost-effective metric that is strongly correlated with SEM metrics, regardless of the oceanographic conditions that those species experienced. These results suggest that an efficient ocean acidification monitoring strategy is to evaluate all pteropod specimens via LDX and to then SEM a subset of those specimens.